Consumer Interest in Consuming Bandung’s Special Culinary on Instagram Social Media: Sentiment Analysis - Yuniati, Ulfa; Kurniadi, Endrian; Ernawati, Resti; Resti Wahab, Nur Indah; Nabilah, Afifah (Jogjakarta Communication Conference (JCC), 2023)
The existence of big data information regarding consumer conversations about culinary, both positive and negative brands, consumer characteristics, customer satisfaction can take advantage of the social media data by business actors to determine the effectiveness of their marketing strategies on Twitter (2). Big data that can be utilized by business actors can be seen from public sentiment through conversations on social media. This study takes texts using #kulinerkhasbandung and #kulinerhalalbandung. The purpose of sentiment analysis is to see positive and negative conversations from text documents and visualizations. Primary data is obtained through observations of consumer activities/interactions that talk about Bandung's culinary specialties on Instagram. This study uses a social network analysis method that focuses on human interaction discussing typical Bandung culinary and halal cuisine. In other words, the measurement and analysis of social networks is mainly based on the ties between actors/nodes. Attributes of actors will help researchers to verify hypotheses of social behavior and analyze certain social phenomena. The population in this study is mention, reply, repost about #kulinerkhasbandung and #kulinerhalalbandung on Instagram social media. In the process of user generated content (UGC) the data collected is a conversation/interaction (17) with #kulinerkhasbandung and #kulinerhalalbandung on Instagram. The research results are in 2022, the movement of talks increased considerably, said to be very good accompanied by neutral comments. As for the hashtag, it can be concluded that batagor, baso, and surabi are Bandung's culinary specialties that are most sought after and in demand by people. The discussion about #kulinerhalalbandung became one of the fourth trending hashtags from #kulinerkhasbandung. This has at least gotten the attention of consumers in the search for #kulinerkhasbandung.